On the organization of excavation and transportation equipment in the coal-bearing zones at open pit mines - Tyulenev Maxim (EDP Sciences, 2021)
One of the essential issues of the benches’ development procedure is the choice of the method of seam development in the complex structure: joint development of rock and coal seams in one complex face or their separate excavation in blocks of 50-100 m in length. The decision of this question is connected with the mode of mining works, represented by the schedule of stripping and winning works. The choice of one or another method is connected with operative-dispatching control of haul trucks delivery. When rock and coal are mined together in a complex face, overburden haul trucks should be supplied for loading rock and coal haul trucks for coal in turns. It is organizationally difficult to supply haul trucks of different purposes during the shift. It is necessary to proceed from the shift (daily) planning of haul trucks supply for specific faces. In addition, it is necessary to take into account that rock and coal faces are often located on opposite sides of the quarry pit. This article studies the issue of organizing the operation of excavation and loading equipment during the mining of the coal-bearing zone of the open pit in order to reduce the loss of output of haul trucks.